Pollen records and time scale for the RM core of the Zoige Basin, northeastern Qinghai-Tibetan Plateau - Shen, CM; Tang, LY; Wang, SM; Li, CH; Liu, KB (Chinese Science Bulletin, 2005)
A continuous pollen record from the Zoige Basin in the northeastern Qinghai-Tibetan Plateau not only provides information on the vegetation and climate changes during the last two glacial/interglacial cycles, but also gives proof to establish the time si-ale of the upper 60 in of the RM core. Subalpine spruce-fir forests colonized the Zoige Basin during the interglacials and interstadials, implying warm and wet climate conditions. Alpine periglacial desert or dry desert may have existed during the penultimate glacial and the last glacial maxima, respectively. Alpine sedge meadow dominated the landscape during MIS 4. The MIS 3 is punctuated by a number of stadials similar to those documented in the Guliya and GISP2 ice cores, as indicated by repeated rise and fall of subalpine spruce-fir forests. Our pollen record reveals a regional climate history similar to those from the neighboring sites, including the Arabian Sea and the Guliya ice core, and thus supports the notion that the Qinghai-Tibetan Plateau acts as an important link between climatic events in the North Atlantic realm and the Asian monsoon domain.